Lessons Learned from Evaluating the Responses of Instrumented Buildings in the United States: The Effects of Supporting Building Characteristics on Floor Response Spectra. Issue 1 (February 2019) - Anajafi, Hamidreza; Medina, Ricardo A.
Floor spectra of many instrumented buildings are evaluated to identify and quantify influential parameters on the horizontal seismic responses of acceleration-sensitive nonstructural components (NSCs). It is shown that many of these parameters are not explicitly incorporated into the American Society of Civil Engineers ASCE 7-16 design equations and are challenging to capture through numerical building models. Significant torsional responses are identified, even for nominally regular buildings, which can increase seismic demands on NSCs located at a floor periphery. For many instrumented buildings, especially single-story ones, floor diaphragms behave as flexible in their plane. This behavior, while mitigating torsional responses, can increase demands on NSCs located away from elements of the lateral-force resisting systems. An evaluation of floor acceleration responses of instrumented buildings with basements reveals that in many cases, even with the presence of perimeter concrete basement walls, accelerations at grade level could be significantly larger than those at lower basement levels. Consideration should be given to establishing the seismic base at the lowermost basement elevation.